STRATEGI MANAJEMEN PERUBAHAN DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR ISLAMIC GREEN SCHOOL KOTA BEKASI - Siti Muslikhah; Baharuddin Baharuddin; Ibnu Muthi (LPPM Universitas Islam 45, 2023)
The purpose of this research is to explain the change management strategy in improving teacher performance in elementary schools, Islamic Green School, Bekasi City. The method used in this study is a qualitative descriptive approach using data collection techniques with the stages of observation, interviews, and documentation. The results of the study show that the change management strategy in improving teacher performance in Islamic Elementary Schools Islamic Green Schools with change management strategies in several areas, namely decision making, curriculum development, students, facilities, educators, financial public relations and inclusion through increased discipline, provision of motivation, exemplary , conduct supervision and evaluation in the form of supervision. Constraints that occur in the change management strategy in improving teacher performance at Islamic Green School Elementary School, a small number of teachers are late to school, are not motivated to improve performance, are not responsive to exemplary leadership and supervision at Islamic Green School Elementary School. The way to overcome obstacles in improving teacher performance is to increase discipline, provide motivation in developing professionalism through training, principals and senior teachers carry out quarterly supervision and coordinate with related parties to complete learning infrastructure.